Peer learning pedagogy model: connecting Kweekschool history with students in the digital age - Aulia Rahman, Sabar; Syafrini, Delmira; Fariza, Muhammad Rio; Dinda Permata, Bunga; Daud, Nathan; Fernandes, Reno (Frontiers in Education, 2026)
IntroductionThis study addresses “Curricular Amnesia,” a systemic structural dysfunction within formal curricula that fails to integrate the physical assets of Senior High School 2 Bukittinggi (formerly Kweekschool) as a permanent spatial framework for collective memory in Southeast Asia. The research aims to analyze this institutional disconnect and formulate an innovative heritage education strategy driven by the digital agency of Generation Z.MethodsUtilizing a qualitative case study approach, data were collected from 13 informants through in-depth interviews with school leaders, teachers, and students, supplemented by non-participatory observations and documentation.ResultsThe findings identify Generation Z’s digital agency as a corrective bottom-up force against institutional failures. Students proactively propose low-cost, high-impact solutions, such as co-creating social media content and storytelling videos, which transform the school’s historical space into a lived experience rather than a dormant monument.DiscussionThe study concludes that peer-to-peer engagement is more effective than top-down pedagogical approaches in restoring collective memory. We propose the “Gen Z-Driven Collective Memory Restoration Framework (GCMRF)” as a strategic model for heritage education, emphasizing that bridging the gap between colonial history and the digital era requires a shift from passive observation to active digital participation.